Resolution of aquaporin-4 antibodies in a woman with neuromyelitis optica treated with human autologous stem cell transplant. Issue 7 (July 2015) - Aouad, Patrick; Li, Jamma; Arthur, Chris; Burt, Richard; Fernando, Suran; Parratt, John
Abstract We report a 47-year-old woman with highly active neuromyelitis optica (NMO) and persistent high titre anti-aquaporin-4 antibodies (anti-AQP-4) who was resistant to multiple immune therapies until she underwent autologous hematopoietic stem cell transplant (auto-HSCT). NMO is the only demyelinating disease with a clinically useful serum biomarker, aquaporin-4, a water channel protein expressed on astrocytes. Anti-AQP-4 antibodies correlate with NMO disease activity and animal models strongly suggest the antibody is pathogenic. Auto-HSCT was associated with clinical and radiological remission, improved disability and resolution of AQP-4 antibodies which are still undetectable 12 months later. The utility of auto-HSCT for refractory NMO warrants further investigation, particularly with regards to pre-conditioning regimens and the utility of AQP-4 antibodies as a biomarker for immunological and clinical remission.